Rice Stripe Mosaic Virus, a Novel Cytorhabdovirus Infecting Rice via Leafhopper Transmission - Yang, Xin; Huang, Jilei; Liu, Chuanhe; Chen, Biao; Zhang, Tong; Zhou, Guohui (Frontiers in Microbiology, 2017)
A new rice viral disease exhibiting distinct symptoms—yellow stripes, mosaic and twisted tips on leaves—was found in China. Electron microscopy of infected leaf cells revealed the presence of bacilliform virions and electron-translucent granular-fibrillar viroplasm in the cytoplasm. The enveloped viral particles were 300 to 375 nm long and 45 to 55 nm wide. The leafhopper Recilia dorsalis was able to transmit the virus to rice seedlings, which subsequently exhibited symptoms similar to those observed in fields. The complete genome of the virus was obtained by small-RNA deep sequencing and reverse transcription-PCR product sequencing. The anti-genome contains seven open reading frames (ORFs). The deduced amino acids of ORF1, ORF5, and ORF7 are, respectively, homologous to the nucleocapsid protein (N), glycoprotein (G), and large polymerase protein (L) of known rhabdoviruses. The predicted product of ORF2 is identified as a phosphoprotein (P) based on its multiple potential phosphorylation sites and 12.6 to 21.0% amino acid (aa) identities with the P proteins of plant rhabdoviruses. The product of ORF4 is presumed to be the viral matrix (M) protein for it shares 10.3 to 14.3% aa identities with those of other rhabdoviruses. The above five products were confirmed as the viral structural proteins by SDS-PAGE and aa sequencing analyses of purified virus preparation. ORF3 and ORF6 are considered to encode two nonstructural proteins with unknown functions. Phylogenetic analysis based on protein N, G, and L amino acid sequences indicated that the isolated virus, which we have tentatively named Rice stripe mosaic virus (RSMV), is a new species in the genus Cytorhabdovirus. To our knowledge, RSMV is the only cytorhabdovirus naturally infecting rice and the first reported leafhopper-transmitted cytorhabdovirus. Our surveys of rice fields indicate that RSMV occurs frequently in Guangdong Province, China. Although the disease incidence is low at present, it might become serious with the vector insect population increasing.